(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role of myths in the context of theories of magic, ritual and culture. The role of magic in society, the structure of rituals and their social significance are highlighted, as well as how myths are interpreted in the disciplines of cultural studies and anthropology.